Derivation and Validation of a Novel Right-Sided Heart Failure Model After Implantation of Continuous Flow Left Ventricular Assist Devices: The EUROMACS (European Registry for Patients with Mechanical Circulatory Support) Right-Sided Heart Failure Risk Score. Issue 9 (27th February 2018) - Soliman, Osama I.I.; Akin, Sakir; Muslem, Rahatullah; Boersma, Eric; Manintveld, Olivier C.; Krabatsch, Thomas; Gummert, Jan F.; de By, Theo M.M.H.; Bogers, Ad J.J.C.; Zijlstra, Felix; Mohacsi, Paul; Caliskan, Kadir
Abstract : Background: The aim of the study was to derive and validate a novel risk score for early right-sided heart failure (RHF) after left ventricular assist device implantation. Methods: The EUROMACS (European Registry for Patients with Mechanical Circulatory Support) was used to identify adult patients undergoing continuous-flow left ventricular assist device implantation with mainstream devices. Eligible patients (n=2988) were randomly divided into derivation (n=2000) and validation (n=988) cohorts. The primary outcome was early (<30 days) severe postoperative RHF, defined as receiving short- or long-term right-sided circulatory support, continuous inotropic support for ≥14 days, or nitric oxide ventilation for ≥48 hours. The secondary outcome was all-cause mortality and length of stay in the intensive care unit. Covariates found to be associated with RHF (exploratory univariate P <0.10) were entered into a multivariable logistic regression model. A risk score was then generated using the relative magnitude of the exponential regression model coefficients of independent predictors at the last step after checking for collinearity, likelihood ratio test, c index, and clinical weight at each step. Results: A 9.5-point risk score incorporating 5 variables (Interagency Registry for Mechanically Assisted Circulatory Support class, use of multiple inotropes, severe right ventricular dysfunction on echocardiography, ratio of right atrial/pulmonary capillary wedge pressure, hemoglobin) was created. The mean scores in the derivation and validation cohorts were 2.7±1.9 and 2.6±2.0, respectively ( P =0.32). RHF in the derivation cohort occurred in 433 patients (21.7%) after left ventricular assist device implantation and was associated with a lower 1-year (53% versus 71%; P <0.001) and 2-year (45% versus 58%; P <0.001) survival compared with patients without RHF. RHF risk ranged from 11% (low risk score 0–2) to 43.1% (high risk score >4; P <0.0001). Median intensive care unit stay was 7 days (interquartile range, 4–15 days) versus 24 days (interquartile range, 14–38 days) in patients without versus with RHF, respectively ( P <0.001). The c index of the composite score was 0.70 in the derivation and 0.67 in the validation cohort. The EUROMACS-RHF risk score outperformed ( P <0.0001) previously published scores and known individual echocardiographic and hemodynamic markers of RHF. Conclusions: This novel EUROMACS-RHF risk score outperformed currently known risk scores and clinical predictors of early postoperative RHF. This novel score may be useful for tailored risk-based clinical assessment and management of patients with advanced HF evaluated for ventricular assist device therapy. Abstract : Supplemental Digital Content is available in the text.